2020
DOI: 10.3390/biom10101384
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Interaction of Ibuprofen with Cholesterol-Containing Lipid Membranes

Abstract: Deciphering the membrane interaction of drug molecules is important for improving drug delivery, cellular uptake, and the understanding of side effects of a given drug molecule. For the anti-inflammatory drug ibuprofen, several studies reported contradictory results regarding the impact of ibuprofen on cholesterol-containing lipid membranes. Here, we investigated membrane localization and orientation as well as the influence of ibuprofen on membrane properties in POPC/cholesterol bilayers using solid-state NMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Ketoprofen [261][262][263][264], Aspirin [199,229,261,[265][266][267][268][269][270][271], Piroxicam [185,261], Ibuprofen [132,166,199,203,265,270,[272][273][274][275][276][277], Indomethacin [277], Diclofenac [132,270], Xanthone derivatives (KS1, KS2, KS3) [278], Indomethacin [279], Carane derivatives [147],…”
Section: Application and Target Drugs And Pharmaceuticsmentioning
confidence: 99%
“…Ketoprofen [261][262][263][264], Aspirin [199,229,261,[265][266][267][268][269][270][271], Piroxicam [185,261], Ibuprofen [132,166,199,203,265,270,[272][273][274][275][276][277], Indomethacin [277], Diclofenac [132,270], Xanthone derivatives (KS1, KS2, KS3) [278], Indomethacin [279], Carane derivatives [147],…”
Section: Application and Target Drugs And Pharmaceuticsmentioning
confidence: 99%
“…In this regard, new data on the processes of interaction of ibuprofen with lipid membranes and with proteins, previously inaccessible for detection and description, could be extremely useful. Different methods, such as X-ray diffraction/scattering [17,18], differential scanning calorimetry [19], quasielastic neutron scattering [20], fluorescence [21], neutron spin echo [22], electrochemical impedance [23], Raman microspectroscopy [24], vibrational sum frequency spectroscopy [25], powder NMR [26] and electron paramagnetic resonance (EPR) spectroscopy [27,28] are used to study ibuprofen-mediated changes in model lipid membranes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, an X-ray scattering and electron density study on a DMPC bilayer containing 20 mol % of cholesterol shows that ibuprofen is expelled from the tail groups (which is a preferred position of ibuprofen in the absence of cholesterol) and partitioned in the head groups . However, a recent study on the effect of ibuprofen on POPC/cholesterol bilayers using solid-state NMR spectroscopy and other biophysical assays reported that ibuprofen disturbs the molecular order of liquid crystalline phospholipid membranes and that the presence of cholesterol in membranes has only a very small effect on the localization of ibuprofen in the model membrane . MD studies of DMPC-based bilayers by Khajeh et al show that ibuprofen prefers to be located in the hydrophobic acyl chain region of DMPC/cholesterol bilayers and causes the ordering of hydrocarbon tails when cholesterol is less than 25 mol %, but when more than 50 mol % cholesterol is present, ibuprofen perturbs and disorders the flexible chains of DMPC and reduces the acyl chain order parameter .…”
Section: Resultsmentioning
confidence: 99%
“…However, the detailed mechanism of action by which cholesterol may influence the drug behavior has not been fully explored . The differential effect of ibuprofen on the lipid bilayer, including cholesterol-containing bilayers, has been previously reported but includes contradictions and thus still requires further elaboration. ,,, …”
Section: Introductionmentioning
confidence: 99%